2014
DOI: 10.1016/j.arr.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Communication breakdown: The impact of ageing on synapse structure

Abstract: Impaired synaptic plasticity is implicated in the functional decline of the nervous system associated with ageing. Understanding the structure of ageing synapses is essential to understanding the functions of these synapses and their role in the ageing nervous system. In this review, we summarize studies on ageing synapses in vertebrates and invertebrates, focusing on changes in morphology and ultrastructure. We cover different parts of the nervous system, including the brain, the retina, the cochlea, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
85
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 142 publications
1
85
1
2
Order By: Relevance
“…Thin spine spinules may be involved in a competition for synapses with neighboring axons, while mushroom spine spinules are involved in remodeling and retrograde signaling. Large mushroom terminals typically have a perforated, or segmented, completely partitioned PSD, and the spinule in many cases may become elongated both into the terminal and also along the active zone membrane; initially its appearance perforates the PSD, and then, as it grows, it completely segments the PSD (Geinisman et al 1994; Ganeshina et al 2004a, b; Stewart et al 2005b; Petralia et al 2014a). As the spinule projection grows, its cross-sectional shape becomes more ridge-like as it divides the PSD (Calverley and Jones 1987; Geinisman et al 1994; Petralia et al 2014a).…”
Section: Synaptic/neuronal Invaginating Projections In More Complex Amentioning
confidence: 99%
See 1 more Smart Citation
“…Thin spine spinules may be involved in a competition for synapses with neighboring axons, while mushroom spine spinules are involved in remodeling and retrograde signaling. Large mushroom terminals typically have a perforated, or segmented, completely partitioned PSD, and the spinule in many cases may become elongated both into the terminal and also along the active zone membrane; initially its appearance perforates the PSD, and then, as it grows, it completely segments the PSD (Geinisman et al 1994; Ganeshina et al 2004a, b; Stewart et al 2005b; Petralia et al 2014a). As the spinule projection grows, its cross-sectional shape becomes more ridge-like as it divides the PSD (Calverley and Jones 1987; Geinisman et al 1994; Petralia et al 2014a).…”
Section: Synaptic/neuronal Invaginating Projections In More Complex Amentioning
confidence: 99%
“…Large mushroom terminals typically have a perforated, or segmented, completely partitioned PSD, and the spinule in many cases may become elongated both into the terminal and also along the active zone membrane; initially its appearance perforates the PSD, and then, as it grows, it completely segments the PSD (Geinisman et al 1994; Ganeshina et al 2004a, b; Stewart et al 2005b; Petralia et al 2014a). As the spinule projection grows, its cross-sectional shape becomes more ridge-like as it divides the PSD (Calverley and Jones 1987; Geinisman et al 1994; Petralia et al 2014a). This appears to be a key component in synaptic plasticity, such as occurs during long-term potentiation (LTP), with many spine synapses going through cycles of structural enlargement and shrinkage related to activity, aging, and changing levels of neurotransmitter receptors (reviewed in Geinisman et al 1994; Geinisman 2000; Stewart et al 2005b; Huganir and Nicoll 2013; Meyer et al 2014; Petralia et al 2014a).…”
Section: Synaptic/neuronal Invaginating Projections In More Complex Amentioning
confidence: 99%
“…For example, aged rats exhibiting impaired spatial memory show a decrease of GR density and their mRNA in the hippocampus (Issa et al, 1990). On the other hand, the aged hippocampus is also characterized by an altered synaptic plasticity with the loss of synapses and deficits in the induction of the long-term potentiation (LTP), a cellular correlate of learning and memory (Petralia et al, 2014). One of the processes involved in the LTP is the increase in the neurotransmitter release which is mediated in part by the activity of presynaptic proteins (Hilfiker et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…2 Changes in synaptic structure and synapse loss with age by neuroanatomical region have been thoroughly reviewed, and the evidence is robust. 3 A recent study found that agedependent declines in cognition and memory may best be explained as a decline in synaptic stability. 4 The monoamine neurotransmitters in brain areas are involved in learning and memory processes and are an essential part of normal synaptic neurotransmission and plasticity.…”
Section: Introductionmentioning
confidence: 99%